Evaluasi dan Perbaikan Proses Bisnis Dengan Business Process Improvement (BPI), Root Cause Analisys (RCA) dan Quality Evaluation Factor (QEF) Pada Layanan Jasa Untuk Pelanggan (Studi Kasus: Kantor Jasa Penilai Publik (KJPP) Aditya Iskandar dan Rekan) - Istania Salma; Nanang Yudi Setiawan; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
KJPP Aditya Iskandar and Rekan is a business entity engaged in the field of Appraisal Services. KJPP Aditya Iskandar and Partners provide several valuation and consultancy services whose process begins with the acceptance of orders from clients, needs of client order object valuation up to delivery of reports to clients. In running the existing business process, there are some activities that do not fit the target so that hamper the company's activities. Therefore the need for evaluation and improvement of business processes. Steps taken to evaluate and improve current business processes are to identify the main business processes and supporters using Value Shop Anaysis, then modeling using Business Process Model and Notation (BPMN), then mapping the quality factor and determining the targets and calculations according to the formula that exists on the QEF (Quality Evaluation Framework) method. After the quality factor and company target is obtained by QEF method, it will search the root of the problem using Root Cause Analysis method with Fishbone Analysis technique. Furthermore, BPI (Business Process Improvement) method is used to get business process improvement recommendation which hope can be used by company to improve existing business process before. Based on the results of simulations conducted improvements to the business process Implementation of Assessment Objects to the Field has increased by 92,68 so that if the process is improved will greatly affect the company activity.